Presence of Escherichia coli of a deaminase and a reductase involved in biosynthesis of riboflavin. - Burrows, R B (1978)
Two enzymes have been partially purified from extracts of Escherchia coli B which together catalyze the conversion of the product of the action of GTP cyclohydrolase II, 2,5-diamino-6-oxy-4-(5'-phosphoribosylamine)pyrimidine, to 5-amino-2,6-dioxy-4-(5'-phosphoribitylamine)pyrimidine. These two compounds are currently thought to be intermediates in the biosynthesis of riboflavin. The enzymatic conversion occurs in two steps. The product of the action of GTP cyclohydrolase II first undergoes hydrolytic deamination at carbon 2 of the ring, followed by reduction of the ribosylamino group to a ribitylamino group. The enzyme which catalyzes the first step, herein called the "deaminase," has been purified 200-fold. The activity was assayed by detecting the conversion of the product of the reaction catalyzed by GTP cyclohydrolase II to a compound which reacts with butanedione to form 6,7-dimethyllumazine. The enzyme has a molecular weight of approximately 80,000 and a pH optimum of 9.1. The dephosphorylated form of the substrate is not deaminated in the presence of the enzyme. The assay for the enzyme which catalyzes the second step, referred to here as the "reductase," involves the detection of the conversion of the product of the deaminase-catalyzed reaction to a compound which, after treatment with alkaline phosphatase, reacts with butanedione to form 6,7-dimethyl-8-ribityllumazine. The reductase has a molecular weight of approximately 40,000 and a pH optimum of 7.5. Like the deaminase, the reductase does not act on the dephosphorylated form of its substrate. Reduced nicotinamide adenine dinucleotide phosphate is required as a cofactor; reduced nicotinamide adenine dinucleotide can be used about 30% as well as the phosphate form. The activity of neither enzyme is inhibited by riboflavin, FMN, or flavine adenine dinucleotide.